PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KARET POLA SWADAYA DI KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Rita Junita; Roza Yulida; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this study are to know what the roles of who already run by agricultural extension in rubber cultivation. This study was conducted at Kuntu and Teluk Paman Village Kampar Kiri District Kampar Regency. The method was used survey method with the samples were 50 farmers of 50 farmers who received counseling. The result showed that role of education has been quite instrumental in activities of non-pattern rubber farming in Kampar Kiri district seen from education, dissemination, facilitation, consultation, supervision, monitoring and evaluation. The average value of the role of education is 3,30 (quite a role), dissemination is 2,60 (quite a role), facilitation with the score 3,28 (quite a role), consultation is 3,10 (quite a role), supervision is 3.06 (quite a role) as well as monitoring and evaluation are 2,83 (quite a role), so that the average overall role of education are 3,00 (quite a role). As for the empowerment of rubber farmers in the district of Kampar Kiri, which includes human resources, productive economy, and institutional power is enough. The average value of human resources is 3,20 (quite helpless), the productive economy is 3,11 (quit helpless) and institutional 3,35 (quite helpless ). So that, the average of the empowerment is 3,22 (quite helpless).   Keywords: The role of education, empowerment, independent rubber farmers